How anxiety attributed to COVID-19, disease knowledge, and intention to vaccinate against SARS-CoV-2 viral infection prevail in general public of Saudi Arabia? - Islam, Md. Ashraful; Alshayban, Dhfer Mahdi; Naqvi, Atta Abbas; Maqsood, Muhammad Bilal; Ishaqui, Azfar Athar; Kashif, Muhammad; Ali, Majid; Haseeb, Abdul (Frontiers in Public Health, 2023)
Aim The study aimed to document the anxiety attributed to COVID-19, disease knowledge, and intention to vaccinate against the disease in general public. Moreover, the interplay among these three outcomes was also investigated. Methods A cross-sectional study was conducted for 2 months in three cities of Dammam Region of Saudi Arabia. The target segment was the adult population of Saudi Arabia. Convenience sampling was used and all adults aged ≥18 were invited to participate. The questionnaire used in the study was available in both Arabic and English languages. It included a demographic section, a section dedicated to vaccination intention and, a section containing coronavirus anxiety scale (CAS). The data analysis was carried out using IBM SPSS version 23. The study was approved by an ethics committee (IRB-2021-05-297). Results A total of 542 responses were analyzed. Most respondents had no anxiety attributed to COVID-19 (92.1%), self-reported good knowledge of COVID-19 (79.7%) and intended to administer a vaccine (57.4%). Age groups 18–29 years and 30–45 years, and having a chronic medical condition, were found to be determinants of having COVID-19 anxiety (p < 0.05). The variables of self-rated good knowledge of disease, never contracted COVID-19, and incomes of SAR 5,000 (i.e., USD 1333), and SAR 7,500–10,000 (i.e., USD 1999.5–2666), were found to be determinants of having positive intention toward vaccination (p < 0.05). Conclusion The anxiety due to COVID-19 was present in a few participants. Besides, self-reported knowledge about COVID-19 and intention to administer a vaccine, were positively linked to each other. However, both variables had no effect on COVID-19 anxiety. It is important to review and address the determinants of positive intention to further increase vaccine acceptance rate.